Acceptance of Distance Learning Technology in Technology-Based Learning Management - Rosita, Tita; Fatmasari, Rhini (JURNAL AL-TANZIM, 2023)
The Technology Acceptance Model (TAM) describes the factors that influence the acceptance and adoption of technology by individuals. In education management, TAM is used to understand how educators, students, and administrative staff respond to the use of technology in the educational process. The application of the Technology Acceptance Model in education management is to help educational institutions plan, implement, and support the use of technology more effectively, taking into account psychological factors and user perceptions. The variables influencing technology acceptance are Perceived Ease of Use, Perceived Usefulness, Attitude Toward Technology, and Intention to Use. This study examines the factors that influence the acceptance of technology by UT postgraduate students toward using information technology in distance learning. The research results are used to develop distance education management, especially in developing internet technology-based learning. The results show that the variables measured have a significant effect on the use of distance learning technology. The Behavioral Intention to Use variable has the most significant influence on Actual Use (AU), followed by the influence of Perceived Ease of Use (PEU) on Attitude Toward Using (ATU) and Perceived Usefulness (PU) on Attitude Toward Using (ATU).Open University, Technology Acceptance Models, Technology Based Learning Management